Ophthalmic consequences of viral hemorrhagic fevers: Insights from the clinic and laboratory - Karnam, Santi; Huang, Ye; Nguyen, Nam; Yeh, Steven (Frontiers in Tropical Diseases, 2023)
Viral hemorrhagic fevers (VHFs) are a diverse group of RNA virus-mediated systemic diseases with significant morbidity and mortality and represent a significant public health concern. Given the high systemic morbidity and mortality in a number of these entities, delays in diagnosis can lead to downstream public health consequences. Many viral hemorrhagic fevers have ophthalmic manifestations and ophthalmologists thus play a key role in disease recognition and the management of ocular complications associated with specific hemorrhagic fevers. This review summarizes the key ophthalmic consequences of viral hemorrhagic fevers, viral disease pathogenesis, disease findings, and areas of unmet research need.